THE ROLE OF CURRENT ACADEMIC PERFORMANCE OF MEDICAL STUDENTS IN PREPARATION FOR THE FINAL EXAM: EXPERIENCE IN TEACHING THE DISCIPLINE «HYGIENE AND ECOLOGY» - BorysenkoАndrii; Antonenko, Anna; Kondratiuk, Mykola; Bardov, Vasyl; Omelchuk, Serhii; Parfonova, Oksana (Eastern Ukrainian Medical Journal, 2025)
Introduction. Current academic performance is a critical indicator of medical students’ preparedness for final examinations. High academic achievements during studies are proven predictors of success in licensing exams. This study examines the changes in academic performance of foreign medical students in the discipline "Hygiene and Ecology" across two academic years, 2023 and 2024, amidst the challenges of the war in Ukraine and their impact on final exam results. The primary focus is on analyzing academic performance, ECTS grade distributions, and their correlations with KROK-2 results to identify predictors of success. Materials and Methods. The study analyzed the results of foreign medical students (Bogomolets National Medical University, 6th-year, "Medicine" specialty) on the KROK-2 exam for the "Hygiene & Health Care Organization" subtest, conducted on 6 June 2023 and 21 May 2024. Academic performance was assessed based on discipline scores, everyday current control scores, and ECTS grades. Statistical analysis was performed using MedStat v.5.2, Microsoft Excel®, and Jupyter Notebook with Python libraries: Pandas, NumPy, SciPy, Scikit-learn, Matplotlib, and Seaborn. Normality of distributions was assessed using the D’Agostino-Pearson and Shapiro-Wilk tests, while comparisons were made using Student’s t-test and Mann-Whitney U test. Statistical significance was set at p < 0.05, with confidence intervals calculated for means and medians. Results. In 2024, a significant increase in the number of students (252 compared to 112 in 2023) was observed, along with shifts in ECTS grade distributions. The percentage of students with grade "E" decreased significantly from 38.4% in 2023 to 12.7% in 2024, while grades "B" and "C" increased notably (from 7.1% to 22.6% and 22.3% to 37.3%, respectively). Mean scores decreased across all grades, with the overall average falling from 72.0 in 2023 to 61.1 in 2024 (p < 0.001). Correlation analysis showed that in 2024, everyday current control scores and discipline scores explained 22.3% (R² = 0.223) and 17.9% (R² = 0.179) of KROK-2 result variance, respectively, compared to 10.6% and 6.4% in 2023. Discussion. The results indicate an improvement in current performance: a decrease in the proportion of students with low grades and a significant increase in the proportion of students with satisfactory ("C") and good ("B") grades. This could be attributed to enhanced learning conditions in 2024, such as stabilization of the educational environment. However, the decline in mean scores suggests the need for targeted interventions, particularly for students in the "C", "D", and "E" grade categories. Statistically significant correlations between KROK-2 results and both discipline and everyday current control scores highlight these as key predictors of success. The stability of "A" grade performance suggests that high-achieving students maintain their outcomes regardless of external challenges. Conclusions. From 2023 to 2024, academic performance improved with fewer students scoring "E" and more achieving "B" and "C" grades. Despite an increase in student numbers, the overall mean scores decreased, emphasizing the need for focused preparation strategies. Correlations between KROK-2 results and academic indicators were stronger in 2024, suggesting these factors became more reliable predictors of success. Interventions should prioritize supporting students in the "C", "D", and "E" categories to further enhance academic outcomes.